2011
DOI: 10.4236/jbise.2011.47062
|View full text |Cite
|
Sign up to set email alerts
|

Bone blood flow is influenced by muscle contractions

Abstract: Forces acting on the skeleton could be divided into those originating from gravitational loading and those originating from muscle loading. Flat bones in a non-weight-baring segment of the skeleton probably experience forces mostly generated by muscle contractions. One purpose of muscle contractions is to generate blood flow within skeletal tissues. The present study aimed to investigate the pulsatile patellar bone blood flow after low and high intensity leg extension exercises. Forty-two healthy individuals v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
(43 reference statements)
0
14
1
Order By: Relevance
“…Twenty‐one studies were identified using near infrared spectroscopy (NIRS) and 10 studies were identified using photoplethysmography (PPG) non‐invasively on in vivo bone tissue . Fifty‐seven studies were identified using laser Doppler flowmetry (LDF) in vivo of which 56 were intra‐operative.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies were identified using near infrared spectroscopy (NIRS) and 10 studies were identified using photoplethysmography (PPG) non‐invasively on in vivo bone tissue . Fifty‐seven studies were identified using laser Doppler flowmetry (LDF) in vivo of which 56 were intra‐operative.…”
Section: Resultsmentioning
confidence: 99%
“…18–22 These studies have shown that NIRS can measure the effects of physiological events on blood perfusion (microgravity 18 , orthostatic stress 19 , aging 21 ). NIRS was also used to assess pulsatile flow in the patella 23,24 . Aziz et al 22 presented hemoglobin content in tibia cortical bone in a single individual during cuff inflation using a NIRS instruments developed specifically for bone.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS was also used to assess pulsatile flow in the patella. 23,24 Aziz et al 22 presented hemoglobin content in tibia cortical bone in a single individual during cuff inflation using a NIRS instruments developed specifically for bone. Sekar et al 25 used timeresolved diffuse optical spectroscopy to probe bone oxygen consumption and blood flow in different superficial bones in able-bodied individuals.…”
mentioning
confidence: 99%
“…An averaging period covering at least 30 -60 heartbeats is suggested to improve confidence in PPG pulse measurements [19], and this time period was used in our study. For further discussions on validation of the PPG method see Hagblad et al [39] and Näslund et al [23].…”
Section: Ppgmentioning
confidence: 99%
“…PPG is a non-invasive optical technique and has been used to monitor blood flow in skin and muscles [17]- [19], but also to monitor hemodynamic sensing in implanted devices [20]. Furthermore, it has been used to study experimentally induced changes in pulsatile blood flow within the patellar bone [21]- [23]. However, the method has not yet been evaluated for hyperbaric use.…”
mentioning
confidence: 99%